TRANSLATION TECHNIQUES USED IN TRANSLATING JOHN GRISHAMâ€™S â€œA TIME TO KILLâ€ NOVEL INTO INDONESIAN. - EVIRIUS NDRURU (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Understanding of the notion of translation techniques as textual analysis instrument in rendering meaning of a language to that of others results in conduction of this research which is designed through employing qualitative research to describe translation techniques and process applied in the translating â€œA Time to Killâ€ novel in Indonesian. Data collection instrument was document. Data analysis was carried out by orientating data analysis technique theory of Miles, Huberman and Saldana in 2014. Additionally, eighteen types of translation techniques of Molina and Hurtado Albir were oriented in describing translation technique types and processes of the application of the translation techniques . As a result, it is found seventeen translation techniques were applied in the translation of the novel. The application of Adaptation technique in the translation of the novel is 4 times, Amplification is 232 times, Borrowing is 96 times, Calque is 55 times, Compensation is 58 times, Description is 3 times, Discursive creation is 56 times, Established equivalent is 6 times, Generalization is 24 times, Linguistic amplification is 41 times, Linguistic compression is 56 times, Literal translation is 322 times, Modulation is 8 times, Particularization is 72 times, Reduction is 80 times, Transposition is 114 times, and Variation 19 times. The process of applying each of those seventeen translation techniques in the translation of the novel is carried out through emphasizing both the source and target language meaning and style. The finding yieds comprehensive insight that translation of â€œA Time to Killâ€ novel in Indonesian is qualified and accurate. Thus, translation technqiues of Molina and Albir are applicable in translating any kind of text.